Tuberculous ventriculitis: A rare complication of central nervous system tuberculosis. Issue 2 (June 2016) - Vaziri, Siavash; Soleiman-Meigooni, Saeed; Rajabi, Jalil; Asgari, Ali
Abstract: Tuberculous ventriculitis is an inflammatory infection of the ventricular system of the brain, and is caused by Mycobacterium tuberculosis . We herein present the case of an immunocompromised patient with brain tuberculomas who developed ventriculitis during treatment. The patient was successfully treated with a high dose of steroid, long-term antituberculosis drugs, and aggressive supportive care.